ADAPTABILITY OF POTATO HYBRIDS WITH COMBINED RESISTANCE TO LATE BLIGHT AND POTATO CYST NEMATODES IN NILGIRI HILLS - Joseph, T. A.; Krishna Prasad, K. S. (Potato Journal, 2013)
Late blight disease (Phytophthora infestans) and potato cyst nematodes (Globodera pallida and Globodera rostochiensis) are the two major plant protection problems of Nilgiri hills where potato can be grown throughout the year. With the onset of monsoons the late blight disease appears every year in an epidemic form in this area and causes severe yield losses. The cyst nematodes, on the other hand, are widely spread in all the major potato growing localities of Nilgiri hills and are being managed by adopting an integrated management practice. During 2001 and 2002 summer crop seasons, two advance hybrids viz., OS/93-D-204 and OS/94-L-956 were evaluated along with two standard controls in replicated field trials at the CPRS farm. The hybrid OS/93-D-204 yielded better than the best control cv. Kufri Giriraj during 2001 and 2002 whereas, the hybrid OS/94-L-956 yielded at par during 2002. Both these hybrids were field resistant to late blight and potato cyst nematodes. These two hybrids were further evaluated in replicated plots at Nanjanad and Theetukkal under farmer’s fields in comparison to standard potato cultivars Kufri Giriraj and Kufri Jyoti during 2003 and 2004. Both these advance hybrids were found to be yielding superior in total and marketable tuber yields than the best control cv. Kufri Giriraj. These studies indicate that the two advance hybrids will be suitable as future varieties for Nilgiris region as they are adapted to local conditions and posses resistance to both species of potato cyst nematodes and late blight disease.